Factors Affecting the Use of Visual Inspection Acetic Acid Test: Multilevel Analysis on the Contextual Effect of Health Center - Siti Kholifah; Uki Retno Budihastuti; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Cervical cancer is one of the deadliest diseases that are a major cause of female morbidity and mortality in developing countries. This study aimed to determine the effect of health centers on the use of visual inspection acetic acid (VIA) tests using social cognitive theory.Subjects and Method: This was an analytic observational study with a cross sectional design, conducted at 25 community health centers (Puskesmas) in Surakarta and Karanganyar, Central Java, Indonesia. A sample of 225 married women at reproductive age was selected by random sampling. The dependent variable was the use of VIA test. The independent variables at level 1 were intention, self-efficacy, attitude, outcome expectation, imitation, type of contraceptive method, distance to health service, belief, and time to attend health services. Puskesmas was independent variable at level 2. The data were collected by questionnaire and analyzed by a multilevel logistic regression.Results: The use of VIA tests was positively affected by intention (b= 1.25; 95% CI= 0.30 to -2.13; p= 0.010), attitude (b= 1.25; 95% CI = 0.30 to -2.13; p= 0.010), outcome expectation (b= 0.86; 95% CI= -0.89 to -0.19; p= 0.076), imitation (b= 1.58; 95% CI= 0.62 to 2.54; p= 0.001), intra uterine device (b= 1.55; 95% CI= 0.65 to 2.45; p= 0.001), distance (b= 1.39; 95% CI= 0.44 to 2.34; p = 0.004), self-efficacy (b= 1.11; 95% CI= 0.26 to 1.97; p= 0.011), trust in health service (b= 1.84; 95% CI= 0.87 to 2.81; p <0.001), and spare time to attend health center (b = 0.76; 95% CI = -0.11 to 1.64; p= 0.090). Puskesmas accreditation status had contextual effect on the use of VIA tests with ICC= 30.68%.Conclusion: The use of VIA tests was positively affected by intention, attitude, outcome expectation, imitation, intrauterine device, distance, self-efficacy, trust in health service, and spare time to attend health center. Puskesmas accreditation status had contextual effect on the use of VIA tests.Keywords: visual inspection acetic acid, social cognitive theory, multilevel analysisCorrespondence: Siti Kholifah. Masters Program in Public Heath, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: olifkholifah53@gmail.com. Mobile: 081575644051.Journal of Health Promotion and Behavior (2019), 4(1): 1-11https://doi.org/10.26911/thejhpb.2019.04.01.01